‘Em Procissão Solene a Deus Orando, para os Batéis Viemos Caminhando’—The Long Ebb-Tide of Catholic Public Piety in the Former-Portuguese Enclave of Macao - Morgan, Stephen (Religions, 2021)
When the City of the Name of God of Macao marked 400 years of Portuguese administration in 1956, the Catholic community’s participation was marked by a wide range of activities that included liturgical celebrations, public processions and other devotions that involved large numbers of the lay faithful, members of confraternities, in addition to the clergy and religious of the enclave. Twenty-one years later the Diocese of Macao celebrated its own quatercentenary with celebrations of a decidedly more sober character and at the retrocession of Macao to Chinese control in December 1999, other than a few liturgical events and hierarchical presence at civic ceremonies, the Church was all but invisible. As the Diocese of Macao plans for its 450th anniversary, some of the former richness has begun to return. This paper outlines the long ebb tide and now-nascent flow of the tide of Catholic public piety in Macao over this period by reference to the Catholic religious processions of the City and seeks to offer tentative explanations grounded in the theological, ecclesial, political and cultural winds that have blown across the Pearl River Delta since the end of the Second World War.
Number: 3